Synthesis, X-ray characterization and DFT calculations of a series of 3-substituted 4, 5-dichloroisothiazoles. Issue 13 (14th March 2023) - Kolesnik, Irina A.; Potkin, Vladimir I.; Grigoriev, Mikhail S.; Novikov, Anton P.; Gomila, Rosa M.; Podrezova, Alexandra G.; Brazhkin, Vadim V.; Zubkov, Fedor I.; Frontera, Antonio
Abstract : This manuscript reports the synthesis and X-ray characterization of a series of 3-substituted 4, 5-dichloroisothiazoles and the analysis of recurrent motifs. Abstract : This manuscript reports a synthetic protocol to obtain 3-substituted 4, 5-dichloroisothiazole derivatives in good yields. This is exemplified by the synthesis of six new compounds, which have been spectroscopically characterized including their solid state structure by single crystal X-ray analysis. As substituents in position 3, both 1, 4-dihydropyridinyl and 4 H -pyranyl moieties have been used, decorated with several groups like cyano, amino, acetyl, ester and methyl, thus providing a variety of possibilities to establish noncovalent interactions. The assemblies have been analysed theoretically, using DFT calculations, molecular electrostatic potential (MEP) surfaces and QTAIM/NCIplot calculations. The π-stacking between the 4, 5-dichloroisothiazole rings is a recurrent motif in the solid state of most compounds, in addition to other less conventional interactions like lone pair (LP)⋯π and halogen bonding contacts. Another interesting motif is the formation of centrosymmetric R22(12) motifs where the cyano groups concurrently establish H-bonds and antiparallel CN⋯CN interactions.